Examining Legal Framework on Administration of Judicial System in Nasarawa State - Okeokwo, ThankGod; Zekeri, Glory Ojomachewu (MultiTech Publisher, 2024)
A judicial system administration is fundamental in determining a civilized society which respects rule of law other than rule of might. The Judges and their Courts play pivotal roles in ensuring justice is served as at when needed without recourse to political, economic and religious considerations. This article examined the legal framework for judicial system in Nasarawa State and aims at associating modern legal framework with the extant legal regime for the judiciary in Nasarawa State. It deployed the doctrinal methodology sourcing data from primary sources like the Nigerian Constitution, High Court of Northern Nigeria Law, Magistrate Courts Law, Area Courts Law. The article found that the extant High Court Law, Magistrate Courts Law and Area Courts Law are those which were promulgated or enacted during the regional system in Nigeria of pre-1966. It was found that some Warrants which established Magistrate Courts and Upper Area Courts in the State were on their face value defective. Recommendations were that the Nasarawa State House of Assembly enacts Laws for the High Court, Magistrate Courts and Area Courts in keeping with judicial system borne from autochthonous laws.